Response of Microbial Communities on Culturing Plates of Post-settlement Sea Cucumbers to Seawater Acidification and Warming - Zhang, Hongxia; Song, Mingshan; Wang, Lili; Zhang, Anguo; Yang, Xiaolong; Liu, Yongjian; Yuan, Xiutang (Frontiers in Marine Science, 2021)
Seawater acidification and warming have been found to affect the early life of many marine organisms, but their effects on the microbial community in the environment related to the early development stage of aquaculture species have been rarely investigated. To understand how seawater acidification and warming impact the microbial community in aquaculture systems, we designed four microcosms to monitor and characterize the microbial composition on the corrugated plates in the Apostichopus japonicus culture tanks during its post-settlement stage. High-throughput 16S rRNA sequencing revealed that the bacterial community composition varied significantly in different periods of incubation. The bacterial diversity and community composition were obviously changed by seawater acidification and warming in the early period and then tended to revert to the level of the control group. Acidification significantly increased the relative abundance of dominant families Rhodobacteraceae and Flavobacteriaceae in the early period, suggesting that microbiota could increase the abundance of predominant taxa to adapt to increased CO2 concentration and reconstruct a stable community structure. No interaction effect of both factors was observed in the combined group. Results reveal that the microbial communities on the corrugated plates in A. japonicus culture tank were affected in the early period of incubation, and could then acclimatize to the increased CO2 and temperature. This study provides new insights into the variation and adaptation responses of the microbiota in aquaculture systems to seawater acidification and warming.